Parallel Tempering Simulation on Generalized Canonical Ensemble (Communications in Computational Physics, 2012)
Parallel tempering simulation is widely used in enhanced sampling of systems with complex energy surfaces. We hereby introduce generalized canonical ensemble (GCE) instead of the usual canonical ensemble into the parallel tempering tofurther improve abilities of the simulation technique. GCE utilizes an adapted weightfunction to obtain a unimodal energy distribution even in phase-coexisting region andthen the parallel tempering on GCE yields the steady swap acceptance rates (SARs)instead of the fluctuated SARs in that on canonical ensemble. With the steady SARs,we can facilitate assign the parameters of the parallel tempering simulation to moreefficiently reach equilibrium among different phases. We illustrate the parallel tempering simulation on GCE in the phase-coexisting region of 2-dimensional Potts model, abenchmark system for new simulation method developing. The result indicates thatthe new parallel tempering method is more efficient to estimate statistical quantities(i.e., to sample the conformational space) than the normal parallel tempering, speciallyin phase-coexisting regions of larger systems.